Comparative Transcriptome Analyses of Schistosoma japonicum Derived From SCID Mice and BALB/c Mice: Clues to the Abnormality in Parasite Growth and Development - Liu, Rong; Cheng, Wen-Jun; Ye, Feng; Zhang, Yao-Dan; Zhong, Qin-Ping; Dong, Hui-Fen; Tang, Hong-Bin; Jiang, Hong (Frontiers in Microbiology, 2020)
Schistosomiasis, caused by the parasitic flatworms called schistosomes, remains one of the most prevailing parasitic disease in the world. The prodigious oviposition of female worms after mature is the main driver of pathology due to infection, yet our understanding about the regulation of development and reproduction of schistosomes is limited. Here we comparatively profiled the transcriptome of Schistosoma japonicum recovered from SCID mice and BALB/c mice, which were collected on the 35th days post infection when prominent morphological abnormalities could be observed in schistosomes from SCID mice, by performing RNA-seq analysis. Of 11,183 identified genes, 62 DEGs with 39 mRNAs up-regulated and 23 mRNAs down-regulated were found in S_M vs. B_M, and 240 DEGs with 152 mRNAs up-regulated and 88 mRNAs down-regulated were found in S_F vs. B_F. We also tested nine DEGs with relatively higher expression abundance in the gonads of the worms (ovary, vitellaria or testis), suggesting their potential biological significance in development and reproduction of the parasites. Gene ontology (GO) enrichment analysis revealed that GO terms such as “microtubule-based process”, “multicellular organismal development” and “Rho protein signal transduction” were significantly enriched in the DEGs in S_F vs. B_F, whereas GO terms such as “oxidation-reduction process”, “response to stress” and “response to DNA damage stimulus” were significantly enriched in the DEGs in S_M vs. B_M. These results revealed that the differential expression of some important genes might contribute to the morphological abnormalities of worms in SCID mice. In further, we selected one DEG, the mitochondrial prohibitin complex protein 1 (Phb1), to perform dsRNA-mediated RNAi in vivo targeting the worms in BALB/c mice, and found it was essential for the growth and reproductive development of both male and female S. japonicum worms. Taken together, these results provided a wealth of information on the differential gene expression profiles of schistosomes from SCID mice when compared with those from BALB/c mice, which were potentially involved in regulating the growth and development of schistosomes. These findings contributed to an understanding of parasite biology, and provided a rich resource for exploitation of antischistosomal intervention targets.